A quantization based robust image watermarking algorithm in the wavelet domain - Potdar, Vidyasagar; Chang, Elizabeth (International Telecommunications Society, 2005)
Watermarking which belong to the field of information hiding has seen a lot of research interest recently. Watermarking is used in B2B and B2C e-commerce markets for a variety of reasons including security, content protection, copyright management, trust management, content authentication, tamper detection and privacy. Recently many watermarking techniques have been proposed to support these applications but one major issue with most of the watermarking techniques it that these techniques fail in the presence of severe attacks. This has been a major threat to content providers in the e-commerce scenario because if the digital content is dramatically changed then it would be difficult to prove the existence of a watermark in it and consequently its ownership. To tackle this security threat towards ownership issues we propose a quantization based watermarking algorithm which offers incredible performance in presence of malicious attacks which try to remove ownership information. The proposed scheme is backed up with excellent results.